The applications of near infra-red fibre bragg grating sensors for wave propagation based structural health monitoring of thin laminated composite plates - Mohd Hafizi, Zohari (2014)
This thesis contributes to the research and development towards achieving better structural health monitoring (SHM) system for composite structures. Composites are widely used in critical engineering applications due to the advantage of higher specific strength and stiffness compared to other conventional materials. However, composite laminates have a very high probability of unexpected damage development during service. This study uses fiber Bragg grating (FBG) sensor to create a practical and robust SHM tool based on monitoring the acoustic emission, in order to provide continuous information of the structure's condition. The remarkable capability of using the FBG sensors for dynamic sensing has been demonstrated, in particular for the wave propagation based SHM. Combined with FBG sensor technologies, the wave propagation based SHM such as acoustic emission (AE), ultrasonic evaluation and acousto-ultrasonics becomes more exciting. The FBG sensor has the ability of acquiring both static and dynamic strains with a single sensor. Besides, the physical size of FBG sensor provides greater access to embed them in composite structures without significantly affecting its structural properties. This study also emphasizes some drawbacks in the use of piezoelectric sensors in the wave propagation based SHM of composite structures, specifically in the AE applications. In most optical fiber based SHM applications to date, people have used only FBG sensors with wavelength 1550 nm. The FBG sensors with this wavelength are commonly used in industries such as telecommunications and health. However, there is an option of using near infra-red (NIR) FBG range which is comparably cheap in terms of total system design, yet offers the same performance of a conventional 1550 nm range FBGs. This research work presents the NIR FBG dynamic sensing system, as a wave propagation-based SHM system for monitoring the damages in thin glass fiber reinforced composite plates. The NIR-FBG sensor system has been validated successfully, in particular for thin composite plate's applications. The sensor system has shown its unique capability whereby it can be applied in the area which cannot be accessed by standard piezoelectric based system. The developed NIR FBG sensor system has shown its competitiveness and ability to replace the piezoelectric sensors in the 'wave propagation based SHM' of laminated composite plates.